2021
DOI: 10.2478/enr-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

ERN1 knockdown modifies the impact of glucose and glutamine deprivations on the expression of EDN1 and its receptors in glioma cells

Abstract: Objective. The aim of the present investigation was to study the impact of glucose and gluta-mine deprivations on the expression of genes encoding EDN1 (endothelin-1), its cognate receptors (EDNRA and EDNRB), and ECE1 (endothelin converting enzyme 1) in U87 glioma cells in response to knockdown of ERN1 (endoplasmic reticulum to nucleus signaling 1), a major signaling pathway of endoplasmic reticulum stress, for evaluation of their possible implication in the control of glioma growth through ERN1 and nutrient l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…These results clearly demonstrated that the expression of PDHA1, PDHB, DLAT, and DLD genes is controlled by glutamine supply and that this control is ER stress dependent particularly through ERN1 signaling. This is in accordance with the data our previous studies (Minchenko et al , 2020(Minchenko et al , 2021Tsymbal et al 2016;Krasnytska et al 2022) as well as studies of other authors (Drogat et al 2007). The changes in PDHA1 and PDHB genes expression under glutamine deprivation are in agreement with data of Yetkin-Arik et al (2019) indicating that silencing of PDHA1 expression prevents the proliferation of HUVECs, because this enzyme of PDH complex is a crucial regulator of pyruvate metabolic pathways (Zaher et al 2021).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results clearly demonstrated that the expression of PDHA1, PDHB, DLAT, and DLD genes is controlled by glutamine supply and that this control is ER stress dependent particularly through ERN1 signaling. This is in accordance with the data our previous studies (Minchenko et al , 2020(Minchenko et al , 2021Tsymbal et al 2016;Krasnytska et al 2022) as well as studies of other authors (Drogat et al 2007). The changes in PDHA1 and PDHB genes expression under glutamine deprivation are in agreement with data of Yetkin-Arik et al (2019) indicating that silencing of PDHA1 expression prevents the proliferation of HUVECs, because this enzyme of PDH complex is a crucial regulator of pyruvate metabolic pathways (Zaher et al 2021).…”
Section: Discussionsupporting
confidence: 94%
“…Glutamine and glucose supply as well as endoplasmic reticulum (ER) stress are very important and complementary factors for the tumor growth. This is also confirmed by the fact that inhibition of endoplasmic reticulum to nucleus signaling 1 (ERN1)/inositol requiring enzyme 1 (IRE1) modifies the effect of glutamine and glucose deprivations on the expression of numerous genes (Minchenko et al , 2015a(Minchenko et al , 2020(Minchenko et al , 2021Tsymbal et al 2016Tsymbal et al , 2020Riabovol et al 2019;Krasnytska et al 2022). Bioinformatics profiling identifies a glucose-related risk signature for the malignancy of glioma (Zhao et al 2017).…”
mentioning
confidence: 82%
“…Minchenko and colleagues demonstrated hypoxic activation of the UPR and upregulation of IRE1 in GBM. Using U87 cell lines with constitutive inhibition of IRE1, they document a complex pattern of downstream gene regulation induced by hypoxia and controlled by IRE1 function [ 11 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that ERN1 knockdown in glioma cells removes the up-regulation of PAX6 and PBXIP1 genes expression introduced by glutamine deprivation and enhances the sensitivity of PBX3 gene expression to this experimental condition. The functional significance of these changes in the expression of PAX6, PBX3, PBXIP1, and MEIS2 genes, which preferentially have diverse impacts on cell proliferation and tumor growth, is under glutamine deprivation condition possibly connected with glutamine deficiency mediated by ERN1 (Auf et al 2010;Zha et al 2014;Li et al 2016Li et al , 2021Khumukcham and Manavathi 2021;Minchenko et al 2021;Wen et al 2021;Wang et al 2022). It is also possible that the endoplasmic reticulum stress mediated by ERN1 creates the resistance to glutamine deprivation and that ERN1 blockade lowers this resistance.…”
Section: Discussionmentioning
confidence: 99%